PERAN KEMASAN PRODUK TERHADAPKEPUTUSAN KONSUMEN DALAM MEMBELIPRODUK JAMU TOLAK ANGIN SIDO MUNCUL (Studi Kasus Pada Pembelian Jamu Tolak Angin Sido Muncul Di Toko Swalayan ADA Bulu Semarang) - Yulekhah Ariyanti (AKSES: Jurnal Ekonomi dan Bisnis, 2014)
The traders assume that the packaging is the sixth factor after “4P” price, place, product, and promotion. It means that product packaging has important role in marketing the products of the  company.  Based on this problem the research tries to explore it by proposing the problem how the influence of product packaging with the variable of visibility, emotional appeal, informastiom, and workability to the purchasing decision and the most dominant variable. In this research the researcher applied the quantitative research method. The samples uses in this research are accidental sampling taken at the Ada Swalayan Bulu Semarang. The instruments of the analysis uses in this research are double linear regression. The hypothesis is examined by determination co-ofecion, F examine (simultaneous examine) t examine (partial examine). The result of the analysis shows the variable of visibility,emotional appeal, information, and workability have significance influence to the purchasing decision. It is proved by high f account > F table (12,502 > 3, 94) with the probability value (0,000) < 0, 05. Partially the result of the analysis shows the variable of  visibility (X1) indicates 2,56, emotional appeal(X2) indicates 1,76, information (X3) indicate 2,074 and workability (X4) indicates 2.283. Visibility, Information and workability gives significance influence the purchasing decisionand  shows that the variable of visibility have domination to purchasing decision. Keywords: purchasing decision, visibility, emotional appeal, information, workability